2011
DOI: 10.3138/ptc.2010-27
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Latent Myofascial Trigger Points on Strength Measurements of the Upper Trapezius: A Case-Controlled Trial

Abstract: Purpose: The purpose of this article was to determine whether strength is altered in the upper trapezius in the presence of latent myofascial trigger points (MTrP). Methods: This study was case controlled and used convenience sampling. The sample recruited was homogeneous with respect to age, sex, height, and body mass. Participants were assessed for the presence of latent MTrP in the upper trapezius and placed into two groups: an experimental group that had latent MTrP in the upper trapezius and a control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 10 publications
(22 reference statements)
0
9
0
Order By: Relevance
“…Our findings are similar to those of other researchers; Gerwin et al [42] found that the presence of the taut band and tender spot were the most reliable diagnosis criteria, and Grieve et al [28] showed that these were also the most prevalent diagnosis criteria. Several authors have included the palpable taut band and the tender spot in LTrP diagnosis, but other diagnosis criteria, such as the referred pain, the jump sign, or the LTR, were not included in several studies [11,16,20,35,43‐46]. Only referred pain may be elicited when the compression used is strong enough [10], and the LTR is the most difficult to elicit by manual palpation; it is inconsistently present in several muscles [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings are similar to those of other researchers; Gerwin et al [42] found that the presence of the taut band and tender spot were the most reliable diagnosis criteria, and Grieve et al [28] showed that these were also the most prevalent diagnosis criteria. Several authors have included the palpable taut band and the tender spot in LTrP diagnosis, but other diagnosis criteria, such as the referred pain, the jump sign, or the LTR, were not included in several studies [11,16,20,35,43‐46]. Only referred pain may be elicited when the compression used is strong enough [10], and the LTR is the most difficult to elicit by manual palpation; it is inconsistently present in several muscles [10].…”
Section: Discussionmentioning
confidence: 99%
“…Another diagnosis criterion proposed for confirming LTrP diagnosis, the ROM limitation, could also be used in our study, because it is an exclusion criterion. However, this diagnostic criterion is not commonly used for the diagnosis of LTrPs [11,16,20,35,43‐46].…”
Section: Discussionmentioning
confidence: 99%
“…The reference contraction should have been done on all subjects to be able to compare all variables between groups with normalised values. Besides this, it is still not clear whether latent MTrPs have an effect on the strength of the muscle involved [ 91 , 92 ]. This muscular effort can influence sEMG in asymptomatic subjects [ 93 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, starting first with inactivation of the LTP cause of the weakness avoids the usual mistake of starting strength training, thus resulting in teaching the patient to use substitutes instead of the inhibited muscle which, unfortunately, can make muscle function more abnormal [27]. In order to examine more closely the changed motor features in CMP patients further studies are needed [14,27].…”
Section: Motor Featuresmentioning
confidence: 99%